IMPLEMENTATION OF PROJECT MANAGEMENT MATURITY MODEL TO IMPROVE THE EFFICIENCY OF ACTIVITY OF LOCAL SELF-GOVERNMENTS - Niema, Oleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the conditions of growing demands of society to the government, project activities cover not only traditional industries, but also the sphere of public administration. Critically important for the success of organization is the team (rather than individual) level of knowledge, skills of staff, and a certain maturity of the organization as a whole in the field of project management. However, the project activities of local self-governments cannot be considered effective or fully compliant with the modern requirements. The level of project competence of management teams of many territorial communities is still not sufficient for the implementation of tasks and functions, the production of relevant project ideas and their successful implementation. The aim of the research is to describe of project management maturity model for its implementation into the activities of the local self-governments from the positions of effectiveness of project management. The entry of the local self-government to a high level of project management maturity will reduce the negative impact of the human factor, systematically focus activities on meeting the needs of the community on a project basis, improve the quality of project management processes, and reduce unproductive costs. Methods used – analysis and synthesis, induction and deduction, logical generalization and comparison.